Integration of Bugis-Makassar Culture Value of Siri’ Na Pacce’ through Social Studies Learning in The Digital Age - Hasni Hasni; Nana Supriatna; Sapriya Sapriya; Murdiyah Winarti; Erlina Wiyanarti (STAI Hubbulwathan Duri, 2022)
This study stems from the phenomenon that social studies learning needs to be developed by creative teachers based on their cultural values. Social studies teachers must be able to understand the problems of social life and develop social skills in their respective cultures. This research aims to describe the cultural values of siri’ na pacce’ for the Bugis-Makassar, and how to integrate these cultural values into social studies learning in the digital age. The research method used is a literature study method by reviewing and identifying the cultural values of siri’ na pacce’ including books, journals, or articles, then presented and analyzed. The cultural value of siri’ na pacce’ for the Bugis-Makassar described in two concepts that characterize the Bugis-Makassar individual to maintain a balance between disgrace and self-esteem which is defined as siri’ and to maintain a sense of togetherness in the position and suffering of each member of the society asserted as pacce’ notion. The integration of siri ‘na pacce’ in social studies learning makes students understand their own culture, able to behave and behave according to customs, such as the application of the spirit of Abulo Sibbatang through the discussion method. Story-based methods by displaying animated videos and images about the persistence of Bugis-Makassar sailors and the story in the script of I La Galigo. Thus that teachers are more creative and innovative in designing interesting learning in the digital age.